2011
DOI: 10.1103/physreve.84.011109
|View full text |Cite
|
Sign up to set email alerts
|

Geometric stochastic resonance in a double cavity

Abstract: Geometric stochastic resonance of particles diffusing across a porous membrane subject to oscillating forces is characterized as a synchronization process. Noninteracting particle currents through a symmetric membrane pore are driven either perpendicular or parallel to the membrane, whereas harmonic-mixing spectral current components are generated by the combined action of perpendicular and parallel drives. In view of potential applications to the transport of colloids and biological molecules through narrow p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 40 publications
3
30
0
Order By: Relevance
“…Previous works have attributed such improvements to the presence of periodic potentials [5][6][7] and to geometric resonance effects. 13 Here, we have shown that uncorrelated thermal noise and zero-mean harmonic disturbance are the minimum ingredients to form synchronization phenomena that lead to diffusion transport enhancement. From the Fokker-Planck equation (12), it is now clear that the mechanisms responsible of the transport enhancement can be drawn from the bilinear term sin (ωt)∂ z P(z, t).…”
Section: Numerical Results From the Fokker-planck Equationmentioning
confidence: 90%
“…Previous works have attributed such improvements to the presence of periodic potentials [5][6][7] and to geometric resonance effects. 13 Here, we have shown that uncorrelated thermal noise and zero-mean harmonic disturbance are the minimum ingredients to form synchronization phenomena that lead to diffusion transport enhancement. From the Fokker-Planck equation (12), it is now clear that the mechanisms responsible of the transport enhancement can be drawn from the bilinear term sin (ωt)∂ z P(z, t).…”
Section: Numerical Results From the Fokker-planck Equationmentioning
confidence: 90%
“…In the opposite case, we have growing excitation modes revealing the linear instability of the system (see also Refs. [67,68] for a discussion in self-gravitating BECs).…”
Section: B Focusing Nonlocal Nonlinearity: Jeans Instabilitymentioning
confidence: 99%
“…It is instructive to mention that space plasmas, particularly the near-Earth plasmas (i.e., ionospheric and auroral plasmas, plasmas in the magnetosphere) have high-energy tails and heat-flux shoulders, and it has been established that such plasmas are best modelled by a distribution rather than by a pure Maxwellian distribution. [35] Furthermore, in the recent past, experimental observations on solar wind plasmas have shown that such plasmas have a spectral index [36] ∼ 2.8, while in the Earth's magnetosphere it is typically in the range [37] 2 ≤ ≤ 8. We therefore, in this paper, have considered weakly dissipative DA solitons in the presence of superthermal particles, and this theoretical analysis has relevance to these environments.…”
Section: Effect Of Dust Concentrationmentioning
confidence: 99%